2019
DOI: 10.1111/1753-0407.12899
|View full text |Cite
|
Sign up to set email alerts
|

Joint effects of folate and vitamin B12 imbalance with maternal characteristics on gestational diabetes mellitus

Abstract: Highlights• Higher folate and lower vitamin B 12 levels were associated with higher glucose and a higher risk of gestational diabetes mellitus (GDM). • The association between folate and vitamin B 12 imbalance and GDM risk can be further modified by maternal risk factors. Abstract Background: This study examined whether folate and vitamin B 12 imbalance is associated with gestational diabetes mellitus (GDM) and explored interactions between B vitamin imbalance and maternal risk factors for GDM. Methods: A cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 26 publications
5
62
1
Order By: Relevance
“…In the end, 17 studies met the selection criteria, 5 of which (Cheng et al., 2019; Huang et al., 2019; Li, Li, et al., 2019; Zhu et al., 2016) used FA supplement or intake instead of folate level as the standard of maternal folate status (Table S1). Therefore, we only included the remaining 12 studies (Barzilay et al., 2018; Berglund et al., 2016; Guven & Cetinkaya, 2005; Idzior‐Waluś et al., 2008; Krishnaveni et al., 2009; Lai et al., 2018; Li, Hou, et al., 2019; Liu et al., 2020; Seghieri et al., 2003; Sukumar et al., 2016; Tarim et al., 2004; Xie et al., 2019) for qualitative and quantitative (meta‐analysis) synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In the end, 17 studies met the selection criteria, 5 of which (Cheng et al., 2019; Huang et al., 2019; Li, Li, et al., 2019; Zhu et al., 2016) used FA supplement or intake instead of folate level as the standard of maternal folate status (Table S1). Therefore, we only included the remaining 12 studies (Barzilay et al., 2018; Berglund et al., 2016; Guven & Cetinkaya, 2005; Idzior‐Waluś et al., 2008; Krishnaveni et al., 2009; Lai et al., 2018; Li, Hou, et al., 2019; Liu et al., 2020; Seghieri et al., 2003; Sukumar et al., 2016; Tarim et al., 2004; Xie et al., 2019) for qualitative and quantitative (meta‐analysis) synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Percentile ratios were categorized into tertiles for the association analyses with the GDM risk. According to previous studies (19), the folate/ vitamin B 12 ratio was also calculated based on their raw data. Moreover, the restricted cubic spline (RCS) regression model with assumed three knots was used to outline the potential nonlinear relations among continuous RBC folate, vitamin B 12 , and GDM risk.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing concerns have risen about supplementing high doses of folic acid to women of reproductive age with low vitamin B 12 intake, although this issue has not been well investigated yet (5). Several casecontrol studies demonstrated that higher serum folate/vitamin B 12 ratio was positively associated with GDM risk (18,19). However, to our knowledge, no studies have investigated the relationship between maternal vitamin B 12 in early pregnancy and GDM.…”
mentioning
confidence: 99%
“…Second, we did not measure the serum concentration of FA before pregnancy or early in pregnancy. Higher FA level in serum was associated with a higher risk of GDM and lower risks of adverse birth outcomes [25,52]. Third, the total FA intake is unknown because we did not consider the FA intake from diet.…”
Section: Discussionmentioning
confidence: 99%
“…The potential confounders included maternal age, education, average monthly household income, postpartum BMI, parity, passive smoking, family history of diabetes, iron supplementation, multivitamin supplementation, gestational dietary intake, and alcohol use. We assessed the interaction between the duration of FA supplementation and multivitamin supplementation on GDM [25]. Generalized linear models were also used to assess the effects of GDM on adverse birth outcomes compared with non-GDM, as well as the effects of FA supplementation for <3 months on adverse birth outcomes.…”
Section: Methodsmentioning
confidence: 99%